2008
DOI: 10.1016/j.molcel.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Analysis of the H3K4 Histone Demethylase RBP2 Reveals a Transcriptional Program Controlling Differentiation

Abstract: SUMMARY Retinoblastoma protein (pRB) mediates cell-cycle withdrawal and differentiation by interacting with a variety of proteins. RB-Binding Protein 2 (RBP2) has been shown to be a key effector. We sought to determine transcriptional regulation by RBP2 genome-wide by using location analysis and gene expression profiling experiments. We describe that RBP2 shows high correlation with the presence of H3K4me3 and its target genes are separated into two functionally distinct classes: differentiation-independent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
142
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(165 citation statements)
references
References 44 publications
21
142
2
Order By: Relevance
“…Consistent with this observation, our previous microarray study showed that correlation between recruitment of KDM5A and decreased transcription was characteristic of the whole group of genes specifically bound by KDM5A in the differentiated condition (9). Besides cell cycle genes, during differentiation KDM5A is bound to genes that code for proteins involved in mitochondrial function and to developmental genes, such as the HOX genes (9,11,21). The coexistence of H3K27me3 and H3K4me3 epitomize the epigenetic state of HOX genes and other developmental genes in stem and progenitor cells.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Consistent with this observation, our previous microarray study showed that correlation between recruitment of KDM5A and decreased transcription was characteristic of the whole group of genes specifically bound by KDM5A in the differentiated condition (9). Besides cell cycle genes, during differentiation KDM5A is bound to genes that code for proteins involved in mitochondrial function and to developmental genes, such as the HOX genes (9,11,21). The coexistence of H3K27me3 and H3K4me3 epitomize the epigenetic state of HOX genes and other developmental genes in stem and progenitor cells.…”
Section: Discussionsupporting
confidence: 80%
“…In quiescent cells, p130/E2F4 is the most prominent pocket protein complex bound to E2F-regulated promoters (3, 6-8). We previously mapped human KDM5A/RBP2 binding regions during differentiation using ChIP-on-chip experiments in diffuse histiocytic lymphoma U937 cells (9). From these two ChIP-on-chip studies, we identified the groups of genes that mapped as condition-specific KDM5A targets (0-h-specific targets, common targets at 0 and 27 h, 27-h-specific targets, common targets at 27 and 96 h, and finally 96-h-specific targets) and DREAM complex targets ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations